Doctors’ Preferences of Anti Histamines : A Comparative Study - Rajyalakshmi, N.; Priya, N. S. (Indian Journal of Marketing, 2006)
The marketers must do more than simply adapt to the needs of target customers. They must provide greater customer value and satisfaction than its competitors do. They also must gain strategic advantage by positioning their offerings strongly against competitors’ offerings in the minds of customers. In order to position their product, the pharmaceutical companies need to know what are the preferences and what is the important factor, the doctors look for, in anti-histamines. This study helps the pharmaceutical companies in general and anti-histamine marketers in particular to identify the key factor to differentiate and position their products